Role of Insurance Sector on Inclusive Growth in India - Debabrata Jana (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
In the present era insurance sector plays a vital role in both developed and developing countries. Insurance markets working as a financial intermediary to contribute economic growth of the country as well as risk management more efficiently.  The purpose of the study is to investigate the relationship between insurance sector development and economic growth in India.  For this study, data has been collected only from the secondary sources for the period 2000 to 2019. To run linear regression, four variables are taken viz. GDP as a surrogate of economic growth and Real Premium Growth Rate, Total Investment in Insurance Sector and Insurance Claim. Finally, it can be suggested that more attention in the insurance market is to be paid so that proper economic growth will be possible in the developing country in India.Keywords: Insurance, Premium, Claim, Investment, GDP.* Bankura Sammilani College, T.G.Samanta Road, Kenduadihi, Bankura, West Bengal 722102, India  ttps://doi.org/10.21632/irjbs.13.2.139-147